2017
DOI: 10.1002/jsfa.8544
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy coupled with independent components analysis to monitor molecular changes during heating and cooling of Cantal‐type cheeses with different NaCl and KCl contents

Abstract: This study demonstrated that SFS can monitor and characterize modification of Cantal-type cheeses at a molecular level, based on the analysis of the fluorescence spectra by ICA. The nature of correlation between signal proportions and the rheological parameters depicted that rheological attributes of cheeses observed at the macroscopic level can be derived from fluorescence spectra. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Intriguingly, the application of spectroscopic methods has been studied to gain insight of the cheese texture and functional characteristics of RSCs (Loudiyi & Ait‐Kaddour, ; Loudiyi & Ait‐Kaddour, ; Loudiyi et al., ). The mid‐infrared spectroscopy was employed to delineate the influence of salt reduction and partial replacement on molecular structural changes of Cantal‐type cheeses.…”
Section: Modern Sensory and Analytical Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the application of spectroscopic methods has been studied to gain insight of the cheese texture and functional characteristics of RSCs (Loudiyi & Ait‐Kaddour, ; Loudiyi & Ait‐Kaddour, ; Loudiyi et al., ). The mid‐infrared spectroscopy was employed to delineate the influence of salt reduction and partial replacement on molecular structural changes of Cantal‐type cheeses.…”
Section: Modern Sensory and Analytical Toolsmentioning
confidence: 99%
“…Loudiyi et al. (, ) tested the molecular and functional properties of reduced‐sodium Cantal‐type cheeses using fluorescence spectroscopy. The authors found differences in the melting and congealing points as measured by rheological method and fluorescence spectroscopy.…”
Section: Modern Sensory and Analytical Toolsmentioning
confidence: 99%
“…The increasing use of this technique has been facilitated by improved instruments and new data analysis techniques such as multivariate and multiway chemometric tools. One of these tools is ICA, which is particularly useful to improve the interpretation of fluorescence data in cases of spectral overlap and changes caused by environmental and matrix effects [15][16][17][18][19][20][21][22][23][24][25]. The main application areas of ICA to handle fluorescence profiles are environmental monitoring and food control.…”
Section: Spectroscopymentioning
confidence: 99%
“…example, Cantal-type cheese with added NaCl and KCl were analyzed for their structure at the molecular level by synchronous fluorescence spectroscopy (SFS) during gentle heating and cooling [19]. ICA treatment revealed three significant components (coenzyme/Maillard reaction products, tryptophan and vitamin A) and their proportions were correlated with rheological measurements to explain cheese texture modifications, which is important for the manufacturing of new cheese products [19].…”
Section: Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation